The role of environmental temperature on movement patterns of giant anteaters - Giroux, Aline (2021)
Mammals can show conspicuous behavioral responses to thermal variation, including changes in movement patterns. We used an integrative approach to understand how environmental temperature can drive the movement behavior of a mammal with low capacity for physiological thermoregulation, the giant anteater (Myrmecophaga tridactyla). We tracked 52 giant anteaters in 7 areas throughout the Brazilian savannah. We estimated the distance moved, area used, use of forest areas, and mean environmental temperature for each monitoring day of each individual. We modeled these data with Mixed Structural Equations — considering the possible interactions between our variables and controlling for sex and body mass. Giant anteaters reduced displacement and increased forest use with decreasing environmental temperature, probably because of their low body heat production. It is possible that they reduce distance moved and area used by reducing the duration of activity. With decreasing temperature, forest habitats become warmer than open ones, besides buffer rain and chilly winds. Reducing displacement and using forests are important strategies to reduce body heat loss and the energetic costs of thermoregulation. However, decreasing movement can limit food access and, consequently, fitness. Therefore, we highlight the importance of forests as thermal shelters. With increasing frequency and intensity of extreme weather events, we showed the need to preserve forest patches to offer suitable conditions for tropical mammals’ behavioral thermoregulation. In this context, policies favoring deforestation on Brazilian territory are especially worrisome. Finally, we emphasize the need of integrative approaches to understand the complex interactions between organisms and the environment.